A Transcriptomic Study Reveals That Fish Vibriosis Due to the Zoonotic Pathogen Vibrio vulnificus Is an Acute Inflammatory Disease in Which Erythrocytes May Play an Important Role - Hernández-Cabanyero, Carla; Sanjuán, Eva; Reyes-López, Felipe E.; Vallejos-Vidal, Eva; Tort, Lluis; Amaro, Carmen (Frontiers in Microbiology, 2022)
Vibrio vulnificus is a marine zoonotic pathogen associated with fish farms that is considered a biomarker of climate change. Zoonotic strains trigger a rapid death of their susceptible hosts (fish or humans) by septicemia that has been linked to a cytokine storm in mice. Therefore, the hypothesis underlying the present work is that V. vulnificus also causes fish death by triggering a cytokine storm in which red blood cells (RBCs), as nucleated cells in fish, could play an active role. To demonstrate this hypothesis, we used the eel immersion infection model and analyzed the transcriptome in RBCs, white BCs and whole blood using an eel-specific microarray platform. Our results demonstrate that V. vulnificus indeed triggers an acute but atypical inflammatory response that occurs in two main phases. The early phase (3 hours post infection [hpi]), is characterized by the upregulation of a number of genes for proinflammatory cytokines related to the mucosal immune response (il17a/f1 and il20) along with genes for antiviral cytokines (il12β) and antiviral factors (ifna and ifnc); while the late phase (12 hpi) is based on the upregulation of genes for typical inflammatory cytokines (il1β), endothelial destruction (mmp9 and hyal2) and, interestingly, genes related to an RNA-based immune response (sidt1). Functional assays revealed significant proteolytic and hemolytic activity in serum at 12 hpi that would explain the hemorrhages characteristic of this septicemia in fish. As expected, we found evidence that RBCs are transcriptionally active and contribute to this atypical immune response, especially in the short term. Based on a selected set of marker genes, we propose here an in vivo RT-qPCR assay that allows detection of early sepsis caused by V. vulnificus. Finally, we develop a model of sepsis that could serve as a basis for understanding sepsis caused by V. vulnificus not only in fish but also in humans.